A metal-free graphdiyne material for highly efficient oxidation of benzene to phenol. (11th August 2021) - Yu, Huidi; Hui, Lan; Fang, Yan; Xue, Yurui; He, Feng; Li, Yuliang
Abstract: Synthesizing active and durable catalysts for oxidizing benzene to phenol through benzene oxidation reaction (BOR) is of great significance for the next-generation phenol industry. The appearance of graphdiyne (GDY) brings us a very excited discovery that we can systematically study on theoretically and experimentally the exact location of active sites and reaction mechanisms of BOR using GDY as the model system. The results give us a clear understanding on the active sites responsible for BOR and sp-hybridized acetylenic bonds in GDY guarantees the activation of benzene molecule by forming new type of '–COO/–COOH' active centers and efficient O transport of BOR kinetics, leading to efficient catalytic performances. The catalytic mechanism and process of GDY are clear and are the first class of metal-free catalysts capable of directly oxidizing benzene to phenol at ambient pressure and room temperature. The catalyst exhibits excellent catalytic activity with the average value of selectivity to be 82.29 ± 2.69% and the conversion to be 8.30 ± 0.66% at low temperature, superior to reported carbon materials.